Neutrino masses in two higgs doublet models - Melo, Téssio Rogério Nóbrega Borja de (2020)
The Standard Model (SM) of Particle Physics provides the most accurate descrip- tion of the behaviour of matter in the smallest accessible distance scales. However, since the SM does not account for the nonzero neutrino masses, dark matter and also is plagued with a number of theoretical issues, it is widely accepted that the SM must be extended. The least understood part of the SM, the scalar sector, have just begun to be probed and the question whether the 125 GeV boson found in the CERN Large Hadron Collider (LHC) is the SM Higgs boson or just one of many scalars from a more complex model is still open. One of the most popular SM extension is the Two Higgs Doublet Model (2HDM), which features two scalar doublets, instead of only one, as in the SM. General 2HDM suffer from excessive Flavor Changing Neutral Interactions (FCNI) due to the presence of extra neutral scalars. Also, the generation of neutrino massesis typically neglected in 2HDM investigations. In this Thesis we study a class of 2HDM which is free from FCNI by means of an Abelian gauge symmetry, which also allows the accommodation of neutrino masses. We discuss several realizations of the seesaw mechanism in this framework, highlighting the phenomenological implications in each case. In particular we study in detail the new Z' gauge boson, investigate the kinetic and mass mixing phenomenology which encompass several constraints coming from atomic parity violation, muon anomalous magnetic moment, rare meson decays, Higgs physics, LEP precision data, neutrino-electron scattering, low energy accelerators and LHC probes.